Attentional Predictors of 5‐month‐olds' Performance on a Looking A‐not‐B Task†. Issue 4 (15th August 2015) - Marcovitch, Stuart; Clearfield, Melissa W.; Swingler, Margaret; Calkins, Susan D.; Bell, Martha Ann
Abstract : In the first year of life, the ability to search for hidden objects is an indicator of object permanence and, when multiple locations are involved, executive function (i.e. inhibition, cognitive flexibility and working memory). The current study was designed to examine attentional predictors of search in 5‐month‐old infants (as measured by the looking A‐not‐B task), and whether levels of maternal education moderated the effect of the predictors. Specifically, in a separate task, the infants were shown a unique puppet, and we measured the percentage of time attending to the puppet, as well as the length of the longest look (i.e., peak fixation) directed towards the puppet. Across the entire sample ( N  = 390), the percentage of time attending to the puppet was positively related to performance on the visual A‐not‐B task. However, for infants whose mothers had not completed college, having a shorter peak looking time (after controlling for percentage of time) was also a predictor of visual A‐not‐B performance. The role of attention, peak fixation and maternal education in visual search is discussed. Copyright © 2015 John Wiley & Sons, Ltd.